The Protective Effects of Hidrosmin and Vitamin C Against Doxorubicin-Induced Sub-Acute Cardiac Toxicity in Rats - Waleed K. Ghanim; Muhsin S. G. Al-Moziel (Iraqi Journal of Pharmaceutical Sciences, 2025)
Doxorubicin is a chemotherapeutic agent belonging to the anthracyclines that are used for the treatment of a wide variety of malignancies, however, it is correlated with serious cardiotoxicity, Hidrosmin is a synthetic flavonoid derived from hesperidin, diosmin which has pleiotropic effects including anti-ischemic, antihypertensive, anti-inflammatory, and antioxidant activities. Vitamin C is a water-soluble may reduce the risks of cardiovascular disease, cancer, and stroke. Forty-five mature male rats their prime weight from 250-280 gm were divided into five groups; Group 1: control group, where rats were injected intraperitoneally with (1ml/kg) of normal saline every other day for fourteen days. Group 2: Rats were injected intraperitoneally with Doxorubicin (2.5 mg/kg), every other day for fourteen days. Group 3: Rats were administered orally hidrosmin daily at a dose (300 mg/kg/day) and injected intraperitoneally with Doxorubicin (2.5 mg/kg) every other day for fourteen days. Group 4: Rats were administered orally vitamin C daily at a dose (100 mg/kg/day) and injected intraperitoneally with Doxorubicin (2.5 mg/kg) every other day for fourteen days. Group 5: Rats were administered orally a combination of hidrosmin at a dose (of 300 mg/kg/day) and vitamin C at a dose (of 100 mg/kg/day) daily and injected intraperitoneally with Doxorubicin (2.5 mg/kg) every other day for fourteen days; on day fifteen animal sacrificed for measurement of troponin I, tumour necrosis factor-alpha, inducible nitric oxide synthase, and histopathological study; hidrosmin significantly (P< 0.05) reduce troponin I, tumour necrosis factor-alpha, inducible nitric oxide synthase and improve histopathological finding when compared with doxorubicin alone.